The Improvement of Student's Critical Thinking Skills on Motion System Material through the Use of Digital Book based on Problem Based Learning - Ernawati, Yuliana; Marianti, Aditya; Saptono, Sigit (Universitas Negeri Semarang)
One of its competency that students must have to face the 4.0 era is the critical thinking skills. These skills can be trained using appropriate learning media, one of which is by using digital books based on problem-based learning. The purpose of this study was to analyze the effectiveness of using problem-based books, problem-based learning materials, and analysis systems on students' critical thinking skills. The research sample was taken using purposive sampling method with a total of 108 students. Based on the results of the study, the average student learning outcomes obtained a score of 67. The results of the N-gain analysis with the medium category showed that digital-based learning problem-based books were effective for improving students' critical thinking skills. The results of the analysis with the Paired Sample t-test showed that the probability value (sig) 0.000 <0.05 means that there are differences in critical thinking skills between before and after using problem-based learning-based digital books. Thus it can be concluded that the use of digital books based on learning materials based on problems with the motion system is effective in improving students' critical thinking skills.